Ceramic Membrane Made from Clay and Kaolin with a Mixture of Coconut Shell Activated Charcoal as a Groundwater Filter - Yulianto, Bambang; Wahyudi, Kristanto; Sudiapermana, Elih; Saepudin, Asep (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
Groundwater if the quality is not good if consumed will have an impact on health. The causes of poor groundwater quality include the value of Fe and Mn levels that exceed the established quality standards. Many methods can be done to overcome the quality of groundwater caused by high Fe and Mn levels, one of which is to use a ceramic membrane made from clay and kaolin with a variation of the coconut shell activated charcoal mixture in the composition of the ceramic membrane by 5%. 10% and 15%. The goal is to determine the effect of ceramic membranes with continuous flow systems on reducing content in clean water. Results showed that the percentage of decrease in Fe and Mn content produced by variations in the composition of coconut shell activated charcoal of 0%, 5%, 10%, and 15% was, respectively for average Fe levels of 15.85%, 69.44%, 75.02%, and 80.83%, and for average Mn levels of 0.00%, 5.71%, 10.00%, and 18.67%. The best variation in the composition of coconut shell-activated charcoal in clay and kaolin-based ceramic membranes in reducing Fe and Mn content in clean water to meet the quality standards of coconut shell-activated charcoal composition by 15%. It is expected that this activity can be used as a basis for further development in groundwater treatment using ceramic membranes made from clay and kaolin with the addition of coconut shell-activated charcoal composition.